The Molecular Mechanisms of the Antibacterial Activity of Sumac (Rhus typhina L.) Tannin Against Pseudomonas aeruginosa - Magdalena Łomanowska; Ewa Olchowik-Grabarek; Krzysztof Czerkas; Nodira Abdulladjanova; Szymon Sękowski (Applied Sciences)
Treatment of infections caused by Pseudomonas aeruginosa presents a challenge due to its ability to adapt and acquire drug resistance rapidly. Therefore, a key challenge is identifying and investigating new compounds with antibacterial and anti-virulence activity. Tannins, a group of plant polyphenolic compounds, can interact with bacterial cells and their virulence factors. The purpose of this study was to assess the antibacterial potential of using 3,6-bis-O-di-O-galloyl-1,2,4-tri-O-galloyl-β-D-glucose (C55H40O34) isolated from Rhus typhina against P. aeruginosa ATCC BAA-1744. The investigation involved viability analyses using the INT assay, fluorescence analyses of the tannins’ interaction with the cell membrane and membrane proteins of P. aeruginosa, and analysis of changes in the Zeta potential. The results obtained allowed us to conclude that C55H40O34 exhibits antimicrobial activity by inducing changes in the biophysical properties of P. aeruginosa’s cell membrane. The thermodynamic parameters indicated that C55H40O34 binds to bacterial membrane proteins through hydrophobic interactions. These interactions with proteins may impact their structure and disrupt their functions, such as disturbing or inhibiting the efflux pumps, which are part of P. aeruginosa’s resistance mechanisms. Therefore, C55H40O34 may be a new, natural agent and could potentially be used against P. aeruginosa.